Patients operated on nodular thyroid diseases - Rubén Elieser Díaz-Samada; Eduardo Valdés Bescosme; Saylin de las Mercedes Casin-Rodríguez; Cesar Alejandro Reina-Cruz; Sinhue Rodríguez-Hung (Universidad Médica Pinareña, 2019)
Introduction: nodular thyroid diseases are relatively frequent, the majority being susceptible to surgical management. Objective: to characterize clinically and surgically the patients operated on nodular thyroid diseases. Method: observational, descriptive and cross-sectional study that was carried out at Dr. Saturnino Lora Torres Provincial Hospital from Santiago de Cuba between 2015 and 2017, the target group was comprised of 150 patients surgically treated due to a thyroid nodule. The information was obtained from the medical records. Medical ethical principles were met. Results: female sex predominated (90 %) and patients between 46 and 60 years old (41,3 %). 80,7 % increased the volume of neck, followed by symptoms of thyroid hypo-function (13,3 %) and dysphagia (12,7 %), as the most frequent clinical manifestations. The preoperative evolution time of 80 patients was greater than one year along with nodular goiter (43,3 %), and cancer (33,3 %) were the most frequent diagnoses, while only 16 % of patients presented thyroid cancer, observing a concordance between the imaging and pathological diagnosis, being hemithyroidectomy (72,7 %) the main surgical technique used, and short-term dysphonia the main postoperative complication (4,0 %). Conclusions: nodular thyroid diseases are more frequent in females and between the third and sixth decades of life, resulting in prolonged evolution and there is a low concordance between diagnostic tests. There were few complications in the series studied.